Donald Davidson : truth, meaning, and knowledge - Żegleń, Urszula M. (Routledge, 1999)
Donald Davidson has made enormous contributions to the philosophy of action, epistemology, semantics and philosophy of mind and today is recognized as one of the most important analytical philosophers of the late twentieth century. Donald Davidson: Truth, Meaning and Knowledge addresses * Davidson's writings on epistemology and theory of language with their implications of ontology and philosophy of mind * the central issue of whether truth is the ultimate goal of enquiry, challenged by contributions from Richard Rorty and Paul Horwich * Davidson's approach to semantics and applied linguistics as addressed by Kirk Ludwig, Gabriel Segal, Peter Pagin, Stephen Neale, Herman Cappelen and Ernie Lepore and Reinaldo Elugardo * Davidson's advances in the philosophy of mind in relation to the views of Williard V. Quine, John McDowell and Peter F. Strawson, in essays by Roger Gibson and Anita Avramides